Frontispiece: Tandem Macrolactone Synthesis: Total Synthesis of (−)‐Exiguolide by a Macrocyclization/Transannular Pyran Cyclization Strategy. Issue 22 (16th May 2022) - Mizukami, Daichi; Iio, Kei; Oda, Mami; Onodera, Yu; Fuwa, Haruhiko
Abstract : Total Synthesis In their Research Article (e202202549 ), Haruhiko Fuwa et al. report the total synthesis of (−)‐exiguolide by a macrocyclization/transannular pyran cyclization strategy.